Transformasi Karakter: Dampak Kesetiaan Guru Kristen dalam Pembentukan Kepribadian Anak Didik - Daniel Udju; Janes Sinaga (PT. Penerbit Tiga Mutiara, 2023)
The aim of this research is to explore and understand in depth the role of a Christian teacher's loyalty in shaping the character of students. This research explores the impact of a Christian teacher's loyalty on the formation of students' character in the context of Christian education. Using a qualitative approach, this research analyzes and presents the findings from literature studies from the Bible, books and journals related to research. The findings show that loyalty to Christian teachers is not just a religious aspect, but an integral foundation that forms the basis of students' character. Teachers' loyalty is reflected in their daily actions, creating an immersive and empowering educational environment. Students respond positively to teachers' loyalty as an inspirational model, forming strong faith values and having a long-term impact on their outlook on life. The practical implications of this research include the development of Christian education strategies that are more effective in forming character. The loyalty of Christian teachers, in the context of this research, is not only a driver of character transformation, but also the key to forming a generation that is firmly rooted in moral and spiritual values.